The first data on subnivean activity of spiders (Arachnida: Aranei) in Southwestern Siberia (Russia) ... - Fomichev, Alexander A.; Koponen, Seppo (Altai State University, 2024)
Thirteen species of spiders from four families were collected using pitfall traps in subnivean habitat in the foothills of Salair Mt. Range, eastern Altai Krai. Linyphiidae predominate in the material. Agroeca limnicunae (McCook, 1884), previously known from Yenisei River in Middle Siberia through Cisokhotia and Alaska to New Jersey (USA), is recorded for the first time in West Siberia and redescribed. The Euro-Uralian boreo-mountainous Maro sublestus Falconer, 1915 is recorded in West Siberia for the first time. A Trans-Palaearctic-NW Nearctic boreal species, Tibioplus diversus (L. Koch, 1879), is reported for the first time from Altai Krai. The winter active spider fauna of eastern Altai Krai consists of species which can be found as adults all year round. All collected species are illustrated. ...